The Morphometric Partial Chronology Tapirus Terrestris (Linnaeus. 1758) in Captivity (Revista Científica Ciencias Naturales y Ambientales, 2012)
This work with the Amazonian Tapir (Tapirus terrestris) was held in the Zoo of Quito in Guayllabamba, during the months of April 2010 to March 2011 were analyzed chronologically somatometry lowland tapir (T. terrestris). Body measurements were made of the tapir having direct contact with tapirs avoiding physical catches ran a total of 25 samples tested with 33 structures, initiating the monitoring on the fifth day of life of the newborn. There was a rapid growth in the first months of life of breeding. The rate of development of each has a domain structure by growth of the structure "I" being the 17,328% of total body and the lowest percentage of growth is the structure "G" with a 0.24%. To achieve record growth chronological tapir cub was found that the body dimensions do not grow regularly as we think, but continues to biological patterns, anatomical and genetic evolution, which determine the rate of growth of each individual's somatic structure due to the role and depending on the habitat they occupy.
Keywords: Tapirus; terrestris; measurements; chronology; morphometry